Oxidative Injury in Ischemic Stroke: A Focus on NADPH Oxidase 4. (3rd February 2022) - Li, Ganglei; Ye, Changsheng; Zhu, Yu; Zhang, Tiesong; Gu, Jun; Pan, Jianwei; Wang, Feng; Wu, Fan; Huang, Kaiyuan; Xu, Kangli; Wu, Xiaomin; Shen, Jian
Abstract : Ischemic stroke is a leading cause of disability and mortality worldwide. Thus, it is urgent to explore its pathophysiological mechanisms and find new therapeutic strategies for its successful treatment. The relationship between oxidative stress and ischemic stroke is increasingly appreciated and attracting considerable attention. ROS serves as a source of oxidative stress. It is a byproduct of mitochondrial metabolism but primarily a functional product of NADPH oxidases (NOX) family members. Nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) is most closely related to the formation of ROS during ischemic stroke. Its expression is significantly upregulated after cerebral ischemia, making it a promising target for treating ischemic stroke. Several drugs targeting NOX4, such as SCM-198, Iso, G-Rb1, betulinic acid, and electroacupuncture, have shown efficacy as treatments of ischemic stroke. MTfp-NOX4 POC provides a novel insight for the treatment of stroke. Combinations of these therapies also provide new approaches for the therapy of ischemic stroke. In this review, we summarize the subcellular location, expression, and pathophysiological mechanisms of NOX4 in the occurrence and development of ischemic stroke. We also discuss the therapeutic strategies and related regulatory mechanisms for treating ischemic stroke. We further comment on the shortcomings of current NOX4-targeted therapy studies and the direction for improvement.